Yield plasticity and molecular diversity analysis in chickpea (Cicer arietinum) - SUPRIYA SACHDEVA; C. BHARADWAJ; SARVJEET SINGH; MANISH ROORKIWAL; VINAY SHARMA; ANUPAM SINGH; RAJEEV VARSHNEY (The Indian Journal of Agricultural Sciences, 2019)
Genetic diversity among 40 chickpea (Cicer arietinum L.) genotypes was investigated using 125 microsatellite (SSR, simple sequence repeat) markers. Twenty five polymorphic markers with average genetic diversity and PIC (Polymorphic Information Content) value of 0.489 and 0.437, respectively, generated a total of 90 alleles. High PIC and gene diversity (HE) values indicated good variability amongst the chickpea genotypes. Sequential Agglomerative Hierarchical Non-overlapping (SAHN) grouping revealed two main clusters with 29 genotypes in cluster I and 11 genotypes in cluster II. The Cluster analysis did not follow geographical diversity rather it was in agreement for genetic diversity with respect to seed type and parentage/pedigree. Grouping clearly delineated the diverse kabuli and desi genotypes. Molecular variance analysis also indicated 97% variation within the populations and 3% variation among the populations. Principal coordinate analysis (PCoA) divided all the 40 genotypes into three populations based on their seed type and pedigree. The 2D plot largely supported the dendrogram with similar pattern of clustering. It also indicated that the material used was diverse. Thus, the study proved that SSR markers are informative tools for assessing genetic diversity and can be recommended for characterization studies in chickpea.